Optimalisasi Kontribusi Pajak Daerah dan Retribusi Daerah Terkait Pendapatan Daerah Dalam Rangka Meningkatkan Kemandirian Keuangan Daerah Kota Banjarmasin - Hidayah, Rizky Elmuna; Muhammad Anshar Nur (PPJP ULM, 2024)
This study's objective was to determine the local government's contribution, influence, and policies in optimizing the contribution of regional taxes and regional levies related to regional income in order to increase regional financial independence in the City of Banjarmasin. Using secondary data from the Budget Realization Report of the Central Bureau of Statistics, this descriptive quantitative research uses contribution analysis and multiple linear regression. The results of this study indicate that the contribution of Regional Taxes to Regional Original Income is classified as very good with an average contribution of 60%, while the contribution of Regional Levies is in the poor category with an average contribution of 16%. Furthermore, the contribution of local taxes and regional levies to regional income is still very low because the average contribution is less than 10%. There is a significant influence between Regional Tax Contributions and Regional Levies on Regional Financial Independence.